Аналіз моделей та методів оцінки трудовитрат на забезпечення якості IT-проєктів - Слєпцов, В. А. (ХНУРЕ, 2024)
This work focuses on the role of labor effort estimation in project quality management, essential in the context of developing information technologies. There are many models and methods for estimating labor costs, each of which considers only some or no project features, so there is an urgent need to develop new approaches that consider the specifics of different projects, their complexity, timeframe, and team characteristics. To increase the accuracy of labor cost estimation in project management, it is proposed to create ensembles of methods for a more individualized and balanced approach, which will have a positive impact on resource planning and management decision-making.
Keywords: оцінка трудовитрат